Ecological Legal Culture In Youth Consciousness And The Philosophical Analysis Of Axiological Foundations - Akbar Safarov; Orzu Omonturdiev (Academia One Publishing, 2026)
This article provides a philosophical analysis of the axiological foundations of ecological legal culture in the consciousness of youth. The study examines the interrelation between environmental values, legal awareness, and normative responsibility as key components of sustainable social development. Particular attention is paid to the role of axiological synthesis in shaping young people’s ecological behavior, legal attitudes, and civic engagement within the context of contemporary Uzbekistan. The research emphasizes that ecological legal culture is not limited to knowledge of environmental legislation, it also includes value-based orientations, ethical motivation, and the internalization of legal norms as personal and social responsibilities. The article argues that the development of ecological legal culture among youth requires an integrated approach combining philosophical reflection, legal education, and social practice.
Keywords: Ecological legal culture; youth; axiology